Measurements of Cardiac Ion Channel Subunits in the Chronic Atrioventricular Block Dog - Akira Takahara; Hirotaka Wagatsuma; Shizuka Aritomi; Tomoyuki Konda; Yasuki Akie; Yuji Nakamura; Atsushi Sugiyama (Elsevier, 2011)
Abstract.: The chronic atrioventricular block (CAVB) dog has been widely used as an in vivo proarrhythmia model. mRNA levels of K+ and Ca2+ channels in the isolated ventricular tissues from normal and CAVB dogs were assayed using a real-time PCR. The mRNA levels of KvLQT1 and MiRP1 were significantly less in the CAVB heart compared with those in the intact heart, whereas no significant difference was detected in the mRNA levels of other K+- or Ca2+-channel subunits. Adaptation against chronic bradycardia-related pathophysiology may have decreased the mRNA levels of cardiac K+ channels, which may partly explain the arrhythmogenic property of this model. Keywords:: chronic atrioventricular block, ion-channel subunit, mRNA